Nilai Tambah dan Tantangan Pendekatan Follow the Money pada Tindak Pidana Bidang Lingkungan Hidup - Haris, Budi Saiful (Pusat Pelaporan dan Analisis Transaksi Keuangan (PPATK), 2024)
Environmental crimes have a wide impact on the country's losses in social and economic development and threaten the sustainability of living things and the ecosystem. In addition, environmental crimes also produce follow-up crimes, namely criminal acts of money laundering (TPPU). Based on the Financial Action Task Force (FATF) July 2021 Report on Money Laundering from Environmental Crimes, environmental crime is one of the crimes that is estimated to generate the most profitable income in the world, which is around USD 110 to 281 billion annually. Unfortunately, the handling of money laundering cases related to environmental crimes in Indonesia remains suboptimal, as evidenced by the disproportionate number of environmental crimes addressed by money laundering authorities in this sector. This study examines how law enforcement of forestry and environmental crimes needs to be strengthened by a follow-the-money approach. This study used descriptive and qualitative analysis methods involving secondary data from various related institutions and primary data from unstructured interviews with several investigators in the field of environment and forestry. The findings of this study indicate that law enforcement in the areas of forestry and environmental protection, particularly in the application of anti-money laundering measures, remains suboptimal. This inadequacy is largely attributed to the limited experience of investigators in handling environmental cases. Whereas, adopting a follow-the-money approach in environmental investigations could significantly enhance the effectiveness of these efforts, allowing for a more comprehensive uncovering of past illegal activities. Additionally, this approach has the potential to identify a broader network of involved parties, including the identification of beneficial owners.